White matter hyperintensities in cholinergic pathways are associated with dementia severity in e4 carriers but not in non-carriers - Yu, Ming-Chun; Chuang, Yi-Fang; Wu, Shu-Ching; Ho, Cheng-Feng; Liu, Yi-Chien; Chou, Chia-Ju (Frontiers in Neurology, 2023)
Background and objectives: Among individuals with Alzheimer's disease (AD), APOE e4 carriers with increased white matter hyperintensities (WMHs) may selectively be at increased risk of cognitive impairment. Given that the cholinergic system plays a crucial role in cognitive impairment, this study aimed to identify how APOE status modulates the associations between dementia severity and white matter hyperintensities in cholinergic pathways. Methods: From 2018 to 2022, we recruited participants (APOE e4 carriers, n=49; noncarriers, n=117) from the memory clinic of Cardinal Tien Hospital, Taipei, Taiwan. Participants underwent brain MRI, neuropsychological testing, and APOE genotyping. In this study, we applied the visual rating scale of the Cholinergic Pathways Hyperintensities Scale (CHIPS) to evaluate WMHs in cholinergic pathways compared with the Fazekas scale. Multiple regression was used to assess the influence of CHIPS score and APOE carrier status on dementia severity based on Clinical Dementia Rating - Sum of Boxes (CDR-SB). Results: After adjusting for age, education and sex, higher CHIPS scores tended to be associated with higher CDR-SB in APOE e4 carriers but not in the noncarrier group. Conclusions: Carriers and noncarriers present distinct associations between dementia severity and WMHs in cholinergic pathways. In APOE e4 carriers, increased white matter in cholinergic pathways are associated with greater dementia severity. In noncarriers, WMHs exhibit less predictive roles for clinical dementia severity. WMHs on the cholinergic pathway may have a different impact on APOE e4 carriers versus non-carriers.